ผลของโปรแกรมการเสริมสร้างแรงจูงใจอย่างต่อเนื่องทางโทรศัพท์ต่อพฤติกรรมการดื่มสุราของผู้ติดสุรา - ญาดา บุตรปัญญา (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study is a quasi-experimental two groups pre – post test design. The objectives of the study were to compare: 1) Alcohol consumption in person with alcohol dependence before and after received countinuing motivational interviewing telephone – based program and 2) Alcohol consumption in person with alcohol dependence between persons who received countinuing motivational interviewing telephone – based program and those who received regular care. The sample consisted of 40 persons attended alcohol dependence treatment program at Phramongkutklao hospital. They were matched pairs with scores on Alcohol Use Identification Test (AUDIT) then randomly assigned to the experimental and control groups, 20 subjects in each group. The experimental group received countinuing motivational interviewing telephone – based program and the control groups received regular care. The study instruments composed of 1) countinuing motivational interviewing telephone – based program 2) The Alcohol Consumption Assessment (ACA ) and 3) SOCRATES – 8A. The 1st, 2nd and 3rd instruments were verified for content validity by 5 professional experts. The reliability of the 2nd instruments was reported by Pearson correction as of 1 and the 3rd instruments had Cronbach’s Alpha Coefficient reliability of .82. The data was analyzed using descriptive statistics and t – test at .05 level. Major findings are as follows : 1. Alcohol consumption in person with alcohol dependence who received countinuing motivational interviewing telephone– based program was significantly lower than that before at p .05; 2. Alcohol consumption in person with alcohol dependence who received countinuing motivational interviewing telephone – based program was significantly lower than those who received the regular care at p .05.